Specifics of Management of the Personnel Capacity of Municipality in the Conditions of Reform of Local Government - Elena Nikolaevna Malik; Aleksey Viktorovich Melnikov (Управленческое консультирование)
Basis of effective work of local governments is their personnel structure. Efficiency of activity of local governments in many respects is defined by quality of their personnel structure, its ability and readiness for the solution of problems of municipal management in constantly changing and becoming complicated conditions of reforming of system of local government as independent level of management. Authors of article believe that in the conditions of reforming of local government deficiency of the qualified and competent shots is observed. Formation of the highly professional and competent personnel case of municipal service with the corresponding personnel potential, optimization of management of its development is represented essentially important condition of successful realization of reform of local government and the solution of questions of local value. In modern conditions for ensuring quality of life ability of local governments to organize and coordinate functioning of all subsystems of municipality, and also to reveal objectively existing needs of local community for receiving support of the state is decisive. The system of training has to be complex, perspective, obligatory for all employees of local governments.